حروف الجر ومعانيها الأصلية والفرعية - Danial Jamal (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2017)
Jar (preposition) is a word that binds a word to another in a sentence. Thus, these words can be fully understood. Therefore, the jar has an important role in Arabic. In addition, the jar becomes one of the most commonly used words in everyday life. However, it has a uniqueness that to be known, in which the jar has a basic meaning on one side, and is also homonym on the other. Therefore, the jar is sometimes unintelligible based on its original meaning but with other meanings italso contains. These other meanings are present when the context or text of sentence is to be desired. This paper discuss variousmeanings of jar accompaniedby an emphasis on the basic meaning it has.